Las revoluciones burguesas / Eric J. Hobsbawm ; [traducción, Felipe Ximénez de Sandoval] - Ximénez de Sandoval, Felipe; Hobsbawm, E. J. (Eric J.) (1917-2012) (Punto Omega. Historia social y política ; 249)
Contiene: Vol. I - Vol. II